Development and Validation of Muslim Moral Emotions Inventory (MMEI) - Rezki Perdani Sawai; Sidek Mohd Noah; Abdul Rashid Abdul Aziz; Roslee Ahmad; Joki Perdani Sawai (Human Resource Management Academic Research Society, 2024)
Indexed by ERA